2019
DOI: 10.12982/cmujns.2019.0027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory, Analgesic, and Antipyretic Activities of Pseuderanthemum palatiferum

Abstract: The objectives of this study were to evaluate the anti-inflammatory, analgesic, and antipyretic activities of water extract from fresh leaves of Pseuderanthemum palatiferum (WEPP).The anti-inflammatory activity of WEPP was evaluated in ethylphenylpropiolate (EPP)-induced ear edema, carrageenan-induced paw edema, arachidonic acid (AA)-induced paw edema, and cotton pellet-induced granuloma experiments. Acetic acid-induced writhing and tail-flick experiments were conducted to evaluate analgesic activity. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…22 In an animal model, it was shown that oral administration of aqueous extract of the plant leaves (600 mg/kg) considerably suppressed paw edema induced by carrageenan and arachidonic acid. 4 Despite limited data about in vivo anti-inflammatory effects and human trials of the plant are available, the findings from these studies above altogether highlighted that P. palatiferum may be suitable for developing plantderived anti-inflammatory drugs.…”
Section: Inhibition Of Bovine Albumin Denaturationmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In an animal model, it was shown that oral administration of aqueous extract of the plant leaves (600 mg/kg) considerably suppressed paw edema induced by carrageenan and arachidonic acid. 4 Despite limited data about in vivo anti-inflammatory effects and human trials of the plant are available, the findings from these studies above altogether highlighted that P. palatiferum may be suitable for developing plantderived anti-inflammatory drugs.…”
Section: Inhibition Of Bovine Albumin Denaturationmentioning
confidence: 99%
“…For example, oral administration of fresh leaf aqueous extracts (0.6 g/kg) considerably suppressed paw edema induced by carrageenan (57%) and arachidonic acid (47%) in rats. 4 An oral glucose tolerance test in streptozotocin-nicotinamide-induced diabetic rats showed that leaf aqueous extract (0.25 g/kg and 0.50 g/kg) exerted hypoglycemic effects. 5 Leaf aqueous extracts also displayed anticancer activity by inhibiting cell viability and induce ROS-mediated mitochondrial related apoptosis in A549 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As the potential botanical applications to treat chronic diseases of the plant, however, the fresh leaf of P. palatiferum has been used. The water extract from the leaf of P. palatiferum reveals the hypotensive and bradycardic activities (Khonsung et al, 2011), anti-inflammatory and analgesic activities (Inchab et al, 2019), and gastroprotective activity (Inchab et al, 2018). This study aimed to assess acute and ninety-day oral toxicity of the water extract of the fresh leaf of P. palatiferum in rats because some signs and symptoms of toxicity may appear after repeated exposure.…”
Section: Introductionmentioning
confidence: 99%